Peran Kanal Youtube Sumeks Minggu Dalam Menyajikan Informasi Sosial Budaya Di Ogan Komering Ilir - Farhan Hamzah; Nurseri Hasnah Nasution; Muslimin (CV. ITTC INDONESIA, 2024)
YouTube is a website portal that provides video sharing services. Users who have registered can upload their videos to the YouTube server so that they can be seen by internet audiences throughout the world. The videos uploaded are usually personal videos of the users. Sumeks Minggu is a news agency located in Sukamulya village, Sumeks Minggu is a trusted media in presenting socio-cultural information in Ogan Komering Ilir Regency, especially the Air Sugihan area. Sumeks Minggu plays a very important role in presenting socio-cultural news in Ogan Komering Ilir, The news topics presented are about conflicts that occur in society, education, sports, culture, development, and entertainment and others. Sumeks Minggu provides space for the people of Air Sugihan to be more open to the outside world, and also encourages people to be braver in overcoming social conflicts. Sumeks Minggu is also present as a trusted media, always capturing important moments that occur in Ogan Komering Ilir. Social culture is an order and interaction in people's lives which includes elements such as customs, knowledge, beliefs and morals. Social culture that develops in a society can experience changes driven by factors such as globalization and external influences this, among other things, results in acculturation and assimilation. Meanwhile, the inhibiting factors in socio-cultural change are the isolated situation of society and its conservative nature. The methodology that the author uses is descriptive qualitative. The researcher carries out direct observations at the research location to conduct interviews and documentation, The author took samples by analyzing all posts in the period 27 November until 27 December 2023 which contains elements of Social and Cultural Information on Ogan Komering Ilir, totaling 147 Videos, 80 Shorts, 6 Live. The role of the Sumeks Minggu Youtube Channel is to help convey socio-cultural information in Ogan Komering Ilir, and convey the aspirations of the Air Sugihan Community who have criticism, opinions and hopes to obtain their rights as Indonesian citizens.